The illegitimacy of nationalism : Rabindranath Tagore and the politics of self - Nandy, Ashis (Delhi ; New York : Oxford University Press, 1994)
Analysis of Rabindranath Tagore's views on nationalism in India.
Includes index.
Keywords: Tagore, Rabindranath, -- 1861-1941 -- Political and social views; Nationalism